طرق تلقي الحديث عند الصحابة -رضوان الله عليهم- بعد مماته صلى الله عليه وسلم - Shumsudin Yabi; Aminudin Basir@Ahmad; Fadlan bin Mohd Othman; Ali Samoh; Akila Mamat; Norhasnira Ibrahim (Universiti Kebangsaan Malaysia (UKM), 2024)
Volume :4 No:1